2020
DOI: 10.1101/2020.02.08.939819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond range size: drivers of species’ geographic range structure in European plants

Abstract: Beyond range size: drivers of species' geographic range structure in European plants 1 2 Running title: Geographic range structure of European plant species 3 4 Abstract 5 Aim: To assess if and how species' range size relates to range structure, if the observed 6 geographic range properties can be retrieved from predicted maps based on species distribution 7 modeling, and whether range properties are predictable from biogeophysical factors.8 Location: Europe 9 Time period: Current 10 Major taxa studied: 813 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Exploring how internal range structure is environmentally determined is an emerging field. In general, the factors influencing internal structure of a geographical range are expected to differ from those affecting geographical range boundaries 57 . Recent research has revealed that climate change can modify internal range structure independently from range edges, which may arise if metapopulation viability differs between range interior and range edges 58 .…”
Section: Shadow Distributions and Spatial Drivers Of Geographic Distr...mentioning
confidence: 99%
“…Exploring how internal range structure is environmentally determined is an emerging field. In general, the factors influencing internal structure of a geographical range are expected to differ from those affecting geographical range boundaries 57 . Recent research has revealed that climate change can modify internal range structure independently from range edges, which may arise if metapopulation viability differs between range interior and range edges 58 .…”
Section: Shadow Distributions and Spatial Drivers Of Geographic Distr...mentioning
confidence: 99%
“…Range shifts are therefore key to species persistence (Muir et al, 2020). Beyond range size and boundaries, internal range structure metrics are needed to adequately | 643 describe species' ranges and more accurately quantify how they will be affected in the future (Csergő et al, 2020), particularly for species with discontinuous distributions. Analysing which landscape-level processes scale up to structure species biogeographic ranges has however remained largely unexplored.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…the external range structure), thus overlooking changes taking place within ranges (i.e. the internal range structure; Csergő et al, 2020).…”
Section: Introductionmentioning
confidence: 99%